Clinicopathologic predictors of outcomes in children with stage I testicular germ cell tumors: A pooled post hoc analysis of trials from the Children's Oncology Group. Issue 4 (August 2022) - Singla, Nirmish; Wong, Justin; Singla, Shyamli; Krailo, Mark; Huang, Li; Shaikh, Furqan; Billmire, Deborah; Rescorla, Frederick; Ross, Jonathon; Dicken, Bryan; Amatruda, James F.; Lindsay Frazier, A.; et al.
Summary: Background: Patients with clinical stage I (CS I: cN0M0) testicular germ cell tumors (TGCT) exhibit favorable oncologic outcomes. While prognostic features can help inform treatment in adults with CS I TGCT, we lack reliable means to predict relapse among pediatric and adolescent patients. Objective: We sought to identify predictors of relapse in children with CS I TGCT. Study design: We performed a pooled post hoc analysis on pediatric and adolescent AJCC CS I TGCT patients enrolled in 3 prospective trials: INT-0097 (phase II), INT-0106 (phase III), and AGCT0132 (phase III). Pathology was centrally reviewed. Patient demographics, pT stage, serum tumor markers, margin status, histology, relapse, and survival were compiled. Cox regression analyses were used to identify predictors of events, defined as relapse, secondary malignant neoplasm, or death. Results: 106 patients were identified with outcomes data available. Most patients were pT1-2 stage. Among patients with evaluable histopathology, yolk sac tumor elements were present in all patients and lymphovascular invasion in 51% of patients. Over a median follow-up of 56 months, no patients died, and 25 patients (24%) experienced an event (median event-free survival not reached). Independent predictors of events on multivariable analysis included age ≥12 years at diagnosis (HR 8.87, p < 0.001) and higher pT stage (pT2 HR 7.31, p = 0.0017; pT3 HR 13.5, p = 0.0043). Discussion: Although our study population reflects the largest pooled prospective cohort of CS I pediatric and adolescent TGCT to our knowledge, the relatively low event rate limits our multivariable analysis, and longer follow-up duration would help further characterize the natural history of these patients. Centralized pathologic review was also unable to be performed for several patients. Conclusion: Pediatric and adolescent CS I TGCT patients exhibit remarkable 5-year survival. Using combined data from multiple prospective trials, our study identifies clinicopathologic features that predict relapse and inform personalized treatment for these patients by potentially guiding surveillance versus adjuvant treatment strategies. Summary Figure Event free survival by age at diagnosis (A) and pathologic T stage (B). Summary Figure